Cardiovascular risk factors control according to diabetes status and prior cardiovascular events in patients managed in different settings. (October 2020) - Vaccaro, Olga; Vitale, Marilena; Costanzo, Simona; Masulli, Maria; Riccardi, Gabriele; De Curtis, Amalia; Donati, Maria Benedetta; Rivellese, Angela Albarosa; de Gaetano, Giovanni; Iacoviello, Licia
Abstract: Aims: To document in recent cohorts the degree of control of major cardiovascular (CV) risk factors according to diabetes status and prior CV disease in different settings. Methods: We studied men and women aged 50–75 years of whom 3028 with type 2 diabetes mellitus (T2DM) managed at diabetes clinics participants of the TOSCA.IT (NCT00700856) study recruited in 2008–2014; 742 with T2DM managed mainly in primary care and 6753 without diabetes participating in the Moli-sani (NCT03242109) study and recruited in 2005–2010 from an adult general population. Results: Among people without a prior CV event people with diabetes managed at diabetes clinics have lower LDL-cholesterol and blood pressure and a more frequent use of lipid-lowering and antihypertensive medications as compared to people with diabetes managed mainly in primary care and to people without diabetes. The proportions achieving the recommended treatment targets are respectively 47.4% vs 33.4% vs 29.5% for LDL-cholesterol and 42.6% vs 9.5% vs 47.4% for blood pressure. Figures for the participants with prior CV events were 26.8% vs 15.1% vs 42.5% for LDL-cholesterol and 43.8% vs 8.5% vs 43.6% for blood pressure. Conclusions: The study documents that in modern cohorts a large proportion of people with or without diabetes does not achieve the treatment targets for LDL-cholesterol and blood pressure, both in primary and secondary CV prevention. People with diabetes attending diabetes clinics achieve a better control of major CV risk factors than those managed mainly in primary care, thus highlighting the relevant role of a structured model of care.